Evaluación de una plantación de mauritia flexuosa l.f. (aguaje) con fines de manejo sostenido en el centro de investigación y enseñanza forestal puerto almendras, iquitos - Perú - Rodríguez Gómez, Jorge Luis (2008)
The present work developed in the Forestries Faculty of the Amazonía Peruana's University Nacional, He evaluated 2 plantation there is of 16- years sea current of once was installed with handling ends sustained with different separations. The parameters evaluados went : individuals's number with and without stipes, total and partial height, inclination and orientation angle of turning of the leaves, alive leaves, heavy loss of life and survival number and also the ground where the plantation grows was examined. The statistical design was the one with blocks unrestrictedly at random with 2 repetitions, whose aftermaths submitted to the ANVA; Them as they indicate to exist you tell apart significant enter total and partial, the presence of stipe, the heights the survival and the separations; In like manner due to the little plants number with flowers observed after 16 years of having established the plantation, it is not possible establishing relations among the inclination angle and the turning orientation of the leaves with plant's sex. He found a 6- green- leaves average for plant and a high survival rate in the neighborhood of the 82. this plantation's grounds come from in the main clayey texture and with 4,98's average pH that is lightly acid.